Promosi Merchandise Band Norbit - Resky Ramadhan; Defrizal saputra (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
Currently in the city of Padang itself, death metal music is also widely favored among young people, marked by the emergence of many local bands in the death metal genre, one of which is called Norbit. Norbit is a Death Metal Cluster from Padang which was born in 2021 with 5 personnel, namely Adan Est as Vocalist, Cruelhammer as Guitarist, Blacksun as Bassist, Shiryo as Drummer and Juggernaut as Guitarist. The first single released by Norbit is titled Genocide. The number of metal bands like Norbit that develop in the middle of Padang city is a challenge for Norbit to compete, especially in introducing Norbit to the public and metal band lovers. One form of introduction is merchandise promotion. Based on the results of initial interviews with Norbit's vocalist about the promotion of merchandise clothes that have been done, it appears that the promotion of merchandise that has been done before is less effective and does not increase sales of Norbit clothes. The main media design that the author will use is in the form of promotional videos with cinematic techniques that will be published on social media such as Youtube and Instagram.The design of Norbit band merchandise promotion uses the Glass Box method, a rational thinking method that objectively and systematically examines things logically and is free from irrational thoughts and considerations.